Assessment of Water Quality Parameters by Using the Multidimensional Scaling Analysis - Suheyla Yerel; Huseyin Ankara (E-Journal of Chemistry)
The surface water quality parameters of the western region of Black Sea in Turkey were assessed by using multidimensional scaling analysis. This technique was applied to the surface water quality parameters obtained from the five monitoring stations. Multidimensional scaling analysis showed that Cl-, SO42-, Na+ and BOD5 are the most important parameters causing difference in the monitoring stations. These analysis results present from the domestic waste and organic pollution affected of surface water quality. Thus, this study represents the usefulness of multidimensional scaling analysis for interpretation in the river pollution problems.